Comparative Analysis of Inheritance Verses in The Qur'an: Hamka and Hazairin's Interpretations and Their Relevance in Modern Social Context - Muhammad Thohir Ihsan; Imron Rosyadi; Mohammad Zakki Azani (Pascasarjana IAI Nasional Laa Roiba Bogor, 2026)
This study compares the interpretations of inheritance verses (Q.S. An-Nisa: 7, 8, 11, 12, 176) by two prominent Indonesian Muslim thinkers, Hamka (Tafsir Al-Azhar) and Hazairin (bilateral inheritance system). Using a qualitative library research method with a comparative (muqaran) approach, framed by Fazlur Rahman's Double Movement theory and Ibn 'Ashur's Maqasid al-Shariah, this study finds that Hamka employs an adab ijtima'i (literary-social) approach emphasizing ethical and distributive justice, protection of vulnerable groups, and moral responsibility within the framework of classical fiqh (patrilineal). Hazairin employs an anthropological-legal approach, constructing a bilateral inheritance system that eliminates the 'ashabah category, recognizes maternal and paternal lineages equally, and introduces the concept of substitute heirs (mawali). Methodologically, Hamka uses tahlili (sequential) method, while Hazairin uses thematic-inductive (mawdu'i). Substantively, Hazairin argues that a daughter can block siblings from inheritance (unlike Hamka's patrilineal position) and that grandchildren from daughters are substitute heirs. Both thinkers share a common goal: social justice, poverty alleviation, and protection of vulnerable groups. Their interpretations are highly relevant for developing fair, contextual, and maqasid-oriented inheritance distribution mechanisms in modern Indonesia.